Modelo de hedge para royalties de petróleo aplicado ao setor público subnacional - Barros Filho, Roberto Gomides de (2017)
In the past few years, several Brazilian subnational governments have developed an extremely high dependency on royalties revenues from the oil and gas exploration, but the financial flow generated by those revenues keep a strong relation with the several market variables like the Brent price, the level of production and the exchange rate. Despite the fact that revenues may oscillate with the market, it is reasonable to assume that Brazilian public expenditures are inflexible in both short and medium term, so the government´s inertia towards market movements may compromise a sound budget policy. This paper intends to propose a hedge strategy for those revenues complying with restrictions imposed by the Brazilian legal framework.